Free Fire Online Game On Language Acquisition Of Children Aged 6-11 Years Old (Psycholinguistics Study) - Damanik, Bernieke Anggita Ristia; Siahaan, Mungkap; Dhillon, Bobby Pramjit Singh; Ningrum, Dinda widya Widya (LPPM Universitas PGRI Sumatera Barat, 2023)
The increasing popularity of online gaming, particularly among children aged 6-11 years old, has raised concerns regarding its potential impact on various aspects of child languange acquisition, including language acquisition. The studied aim to provide an understanding of the relationship between gaming activities and the language learning process. In particular, to provide insight into the potential impact, both positive and negative, of Free Fire online games on children's language acquisition. This research is descriptive qualitative. Data collection techniques used observation method, listening method with basic recording/tapping techniques, and note taking method. The data analysis techniques used are data reduction, data display, and conclusion drawing and verification. the results of the discussion of this research show some positive and negative findings. On the positive side, the children learned English expressions commonly used in the gaming environment, such as “Gloo wall”, “Log-in”, “Bot”, “Low bat”, “Top-up”, “Help”, “Knock”, “By one”, “Lag”, “Done”, “War”, “Jump shot”, “Noob”, “Cheater”, “Damage”, “Fine”, “Join”. They also learn vocabulary in the types of verbs, nouns, adjectives, and adverbs that are directly related to the mechanics and concepts in the Free Fire game. On the negative side, there is exposure to coarse language or swearing in Javanese, such as “asu” and “telek”, which can affect children's language development and behavior. In addition, the emergence of terms such as “noob” and “cheater” may indicate that children are learning unethical behavior in a gaming context.It can be concluded that Free fire online game gave effect on languange acquisition of children 6-11 years old.